The Relation relation Between Nurturing 1000 First Days Of Life With Stunting On Toddlers In Sumberjambe - Sugiarti, Lilis; Setyowati, Lisus; Ermawati, IIt (Jurnal Kesehatan, 2023)
Stunting is a matter which occurs in toddlers and abortive attempt of growth in toddlers which caused by chronic malnutrition, recurrent infections, and inadequate psychosocial stimulations, especially on the First 1000 Days of Life (HPK), from fetus until two years. The aim of this study was analyzed relation between nurturing  1000 first days of life with stunting on toddlers ini Sumberjambe. This study was correlative observational analytic by retrospective approach. Population was Sumberjambe village which the sample are 71 by cluster sampling. Data collecting used questioners, then direct height measurement based on height/age index. This study also examined mom’s characteristics which consist of education, job and income. Dependent variable had 7 indicators namely ANC, Exclusive breastfeeding, iron tabs consumption, provision of deworming drugs, vitamin A, feeding and immunizations. the study’s result showed if there was relation significantly between 1000 first days health maintenance with stunting on toddlers, which showed p value average < 0,05. Most related factor with stunting in Sumberjambe was ANC (p value = 0.000). Therefore, an intensive personal approach is needed to encourage and prevent an increase in ANC visits and to promote good behavior to prevent stunting.